Ghrelin Levels in Children With Intestinal Failure Receiving Long-Term Parenteral Nutrition - Vlug, Lotte E.; Delhanty, Patric J. D.; Neelis, Esther G.; Huisman, Martin; Visser, Jenny A.; Rings, Edmond H. H. M.; Wijnen, René M. H.; Nagelkerke, Sjoerd C. J.; Tabbers, Merit M.; Hulst, Jessie M.; de Koning, Barbara A. E. (Frontiers in Nutrition, 2022)
Background Children with intestinal failure (IF) require parenteral nutrition (PN). Transition to oral and enteral nutrition (EN) can be difficult also due to abnormal gastrointestinal motility. The gut hormone ghrelin is increased in states of negative energy balance, functioning to preserve euglycemia, and also has appetite stimulating and prokinetic properties. We aimed to evaluate and compare ghrelin levels in children with IF, and to assess the relationship with PN-dependency. Methods In this exploratory prospective multicenter study, plasma acylated (AG) and unacylated (UAG) ghrelin levels were measured in children with short bowel syndrome (SBS) and with functional IF (pseudo-obstruction or any enteropathy) and compared with healthy control subjects. Spearman’s rho (rs) was used to assess correlations of AG and UAG with PN-dependency (%PN) and parenteral glucose intake. Results Sixty-four samples from 36 IF-patients were analyzed. Median baseline AG and UAG levels were respectively 279.2 and 101.0 pg/mL in children with SBS (n = 16), 126.4 and 84.5 pg/mL in children with functional IF (n = 20) and 82.4 and 157.3 pg/mL in healthy children (n = 39). AG levels were higher in children with SBS and functional IF than in healthy children (p = 0.002 and p = 0.023, respectively). In SBS, AG positively correlated with %PN (rs = 0.5, p = 0.005) and parenteral glucose intake (rs = 0.6, p = 0.003). These correlations were not observed in functional IF. Conclusion Children with IF had raised AG levels which could be related to starvation of the gut. The positive correlation between AG and glucose infusion rate in SBS suggests an altered glucoregulatory function.